1988
DOI: 10.1002/mrm.1910080311
|View full text |Cite
|
Sign up to set email alerts
|

13C nuclear magnetic resonance spectroscopy of glucose metabolism in human red blood cells

Abstract: Glucose metabolism of human red blood cells was investigated using carbon-13 nuclear magnetic resonance spectroscopy under both oxygenated and nonoxygenated conditions. These results show that under oxygenated conditions reversal of 3-phosphoglyceraldehyde to glucose is in competition with its catabolism to lactate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…13C-enrichment of C3-2,3-DPG was also detected (Pig 1. resonance at c 67.3 ppm). During the first 3 h following the addition of 1-1 3C-glucose, minor 3C-labelling of the C6-and C4-glucose and C3-glucose/-glucose-6phosphate peaks, near 61, 70 and 76ppm, respectively, were alsci observed, indicating that the samples were adequately oxygenated (see Ghai & Gonnella, 1988). Timecourse data of 1-1 3C-glucose consumption and 3-13C-lactate production for all three erythrocyte types are shown in Fig 2. Linear best fit analysis of the kinetics of 1-1 3C-glucose consumption showed that thalassaemia intermedia erythrocytes metabolized glucose almost 3 times faster than both normal and heterozygous red blood cells.…”
Section: Sample Preparationmentioning
confidence: 99%
“…13C-enrichment of C3-2,3-DPG was also detected (Pig 1. resonance at c 67.3 ppm). During the first 3 h following the addition of 1-1 3C-glucose, minor 3C-labelling of the C6-and C4-glucose and C3-glucose/-glucose-6phosphate peaks, near 61, 70 and 76ppm, respectively, were alsci observed, indicating that the samples were adequately oxygenated (see Ghai & Gonnella, 1988). Timecourse data of 1-1 3C-glucose consumption and 3-13C-lactate production for all three erythrocyte types are shown in Fig 2. Linear best fit analysis of the kinetics of 1-1 3C-glucose consumption showed that thalassaemia intermedia erythrocytes metabolized glucose almost 3 times faster than both normal and heterozygous red blood cells.…”
Section: Sample Preparationmentioning
confidence: 99%